Nonspecific blockade of vascular free radical signals by methylated arginine analogues - Pedro,M.A. (1998)
Methylated arginine analogues are often used as probes of the effect of nitric oxide; however, their specificity is unclear and seems to be frequently overestimated. This study analyzed the effects of NG-methyl-L-arginine (L-NMMA) on the endothelium-dependent release of vascular superoxide radicals triggered by increased flow. Plasma ascorbyl radical signals measured by direct electron paramagnetic resonance spectroscopy in 25 rabbits increased by 3.8 ± 0.7 nmol/l vs baseline (28.7 ± 1.4 nmol/l, P<0.001) in response to papaverine-induced flow increases of 121 ± 12%. In contrast, after similar papaverine-induced flow increases simultaneously with L-NMMA infusions, ascorbyl levels were not significantly changed compared to baseline. Similar results were obtained in isolated rabbit aortas perfused ex vivo with the spin trap a-phenyl-N-tert-butylnitrone (N = 22). However, in both preparations, this complete blockade was not reversed by co-infusion of excess L-arginine and was also obtained by N-methyl-D-arginine, thus indicating that it is not related to nitric oxide synthase. L-arginine alone was ineffective, as previously demonstrated for NG-methyl-L-arginine ester (L-NAME). In vitro, neither L-arginine nor its analogues scavenged superoxide radicals. This nonspecific activity of methylated arginine analogues underscores the need for careful controls in order to assess nitric oxide effects, particularly those related to interactions with active oxygen species.